Effect of subsurface pressure on the interface pressure measurement in an in vitro experiment. (March 2020) - Chi, Yung-Wei; Lin, Ray; Tseng, Kuo-Hao; Durbin-Johnson, Blythe
Introduction: It was hypothesized that subsurface pressure (mimicking subcutaneous pressure) variation may affect interface pressure measurement. Method: BISCO® (Rogers, CT) foam was placed on a cylinder cuff model for the experiment. Picopress® and a piezoresistive sensor were used for interface pressure measurement. External pressure was applied using an automated pressure cuff at 40 mmHg. Subsurface pressure mimicking subcutaneous pressure from 3 mmHg to 12 mmHg was generated by a pressure pump underneath the foam. Interface pressure was compared between the true pressure, 40 mmHg, versus Picopress® and the piezoresistive sensor using linear mixed effect model (SAS software, version 9.4, SAS Institute, Cary, NC). Result: Interface pressure measurement using Picopress® did not differ between the incremental subsurface pressures (mean 45.4 ± 0.4) ( P  = 0.54), in contrast to piezoresistive sensor, which demonstrated a difference (mean 42.65 ± 2.7) ( P  < 0.001). This difference appeared to be linearly related. Conclusion: Subsurface pressure mimicking subcutaneous pressure may affect the overall interface pressure measurement according to the piezoresistive sensor but not Picopress®.